Annual Plan 1974-75 Haryana State - Planning Commission (Planning Commission, 1974)
State Government had proposed, an outlay of Rs. 740.00 crores for the Fifth Five Year Plan (1974-79) and Rs. 120.13 crores for the Annual Plan 1974-75, the first year of the Fifth Five Year Plan. Planning Commission have recommended a reduced outlay of Rs.539.23 crores for the Fifth Plan and Rs. 77.07 crores for the Annual Plan 1974-75. However, in the Budget Estimates 1974-75, prevision of Rs. 76.01 crores has been made.
Haryana State